Musical peddy-paper: a collaborative learning activity suported by augmented reality - Gomes, José (2014)
Gaming activities are an integral part of the human learning process, in particular for children. Game-based learning focuses on motivation and children's engagement towards learning. Educational game-based activities are becoming effective strategies to enhance the learning process. This paper presents an educational activity focusing to merge mobile computing devices and Augmented Reality, as a means to engage student in collaborative learning towards the Aesthetical Periods of Music History. The Musical Peddy-paper proposes student to use their mobile computing devices (smartphones/ tablets) to find eight stations scattered in a set location, and then use their music literacy skills to find the correct answer in each station. Collaborative work is required to find the stations and the answers to the clues. The musical Peddy-paper was developed mixing Geo-location and Augmented Reality concepts. Geo-location Points of Interest (POI’s) where set through Hoppala platform. Augmented Reality browsing and QRCode reading is supported by the LAYAR platform. In this paper, we introduce the concept of game-based activities as a tool to promote motivation and engagement towards learning, and fully explain the development process of the activity. We conclude this paper presenting the conclusions contemplating the use of this activity among a group of children from the 2nd Cycle of Basic Education in Basic School Maria Manuela de Sá, Matosinhos – Portugal.